Executive pay transparency and relative performance evaluation: evidence from the 2006 pay disclosure reforms - Choi, Jung Ho; Gipper, Brandon; Shi, Shawn X. (Review of Accounting Studies, 2025)
Early empirical evidence showed a lack of relative performance evaluation (RPE) for executive pay, a surprise given its theoretical appeal. We hypothesize that executive pay transparency can enhance the monitoring of pay practices and increase RPE use. We examine RPE over the two decades centered on the 2006 executive pay disclosure reforms in the United States, which stakeholders—including shareholders, proxy advisors, and compensation consultants—could use to monitor pay plans. Firms that increase disclosures exhibit a significant increase in RPE after the reforms. To understand why, we examine and document that (i) stakeholder attention to pay practices increases after the reform, (ii) stakeholder attention positively relates to increases in RPE, and (iii) say-on-pay voting confirms shareholders’ preference for RPE. Overall, our findings are consistent with executive pay transparency increasing RPE due to enhanced pay monitoring across stakeholders.